PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP AKTIVITAS BELAJAR SISWA KELAS VII PADA MATERI SALING KETERGANTUNGAN DALAM EKOSISTEM - Pratiwi Pratiwi; Erie Agusta (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2018)
Problem-based learning model is a learning activity that requires physical and mental activity of students to understand a learning material through situations and problems presented at the beginning of learning with the aim to train students solve the problems by using problem-solving approach. This study aims to see the effect of problem-based learning model on student learning activities on the material interdependence in the ecosystem VII class. Variables in this research are problem-based learning model as independent variable and learning activity as dependent variable. The sample of this research is VII.C class as experiment class and VII.D class as control class. The method used in this research is all experimental method. Data collection techniques used were questionnaires and observation sheets to determine the level of student learning activity after applied problem-based learning model. H0 rejected and Ha accepted which means there is influence of problem-based learning model to student learning activities on the ecosystem materials.